Digital Communication of BMKG Non-Departmental Government Institutions: Studies on Conveyance of Earthquake Disaster Information via Social Media Twitter @infoBMKG - Kumala Hayati; Ayu Wardani; Nuril Ashivah Misbah (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2023)
BMKG is aware exists urgent information related to earthquakes needed fast movement and accurate messages to society. Besides that, BMKG as an institution non- departmental government has not quite enough answers for open information to the public like disaster earthquakes according to Law No. 14 of 2008 concerning Openness Public Information (KIP). BMKG did digital communication with Twitter platforms to convey information related to the earthquake. So, the problem for this study is how BMKG did digital communication to deliver their information about natural disaster earthquakes through social media Twitter. The study uses a qualitative method. The result of the study This shows that digital communication carried out by BMKG utilizes feature hashtag (#) and keywords earthquake every tweet as a storyteller for convenience user Twitter For the following topic. The topic brings up citizen journalism Because there are two positions users on Twitter as the recipient of messages and sources of the messages alone. So, there is engagement among the public that makes information earthquake the develop in accordance condition latest this makes the image institution government as an information validator earthquake through increasing use of Twitter confirmed.